Atorvastatin population pharmacokinetics in a real‐life setting: Influence of genetic polymorphisms and association with clinical response - Gabriel Stillemans; Adrien Paquot; Giulio G. Muccioli; Emilia Hoste; Nadtha Panin; Anders Åsberg; Jean‐Luc Balligand; Vincent Haufroid; Laure Elens (Wiley, 2022)
Abstract The purpose of this study was to investigate the potential clinical relevance of estimating the apparent clearance (CL/F) of atorvastatin through population pharmacokinetic (PopPK) modeling with samples collected in a real‐life setting in a cohort of ambulatory patients at risk of cardiovascular disease by using an opportunistic sampling strategy easily accessible in clinical routine. A total of 132 pharmacokinetic (PK) samples at a maximum of three visits were collected in the 70 included patients. The effects of demographic, genetic, and clinical covariates were also considered. With the collected data, we developed a two‐compartment PopPK model that allowed estimating atorvastatin CL/F relatively precisely and considering the genotype of the patient for SLCO1B1 c.521T>C single‐nucleotide polymorphism (SNP). Our results indicate that the estimation of the CL/F of atorvastatin through our PopPK model might help in identifying patients at risk of myalgia. Indeed, we showed that a patient presenting a CL/F lower than 414.67 L h−1 is at risk of suffering from muscle discomfort. We also observed that the CL/F was correlated with the efficacy outcomes, suggesting that a higher CL/F is associated with a better drug efficacy (i.e., a greater decrease in total and LDL‐cholesterol levels). In conclusion, our study demonstrates that PopPK modeling can be useful in daily clinics to estimate a patient' atorvastatin clearance. Notifying the clinician with this information can help in identifying patients at risk of myalgia and gives indication about the potential responsiveness to atorvastatin therapy.